(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Adiponectin is an adipocyte-derived hormone with anti-inflammatory, anti-atherogenic, and insulin-sensitizing properties. Reduced adiponectin levels have been associated with obesity, type II diabetes mellitus, and coronary artery disease (CAD). The present study aimed to evaluate the relationship between adiponectin, body mass index (BMI), and glycosylated hemoglobin (HbA1c) in CAD patients with and without type II diabetes mellitus. Methodology: This comparative observational study was conducted in the Department of General Medicine at Sree Mookambika Institute of Medical Sciences from January 2025 to December 2026. A total of 90 subjects were included, among whom 30 patients had CAD with type II diabetes mellitus. Blood samples were collected under aseptic precautions for estimation of serum adiponectin and HbA1c levels. BMI was calculated using standard WHO criteria. Statistical analysis was performed to determine correlations and group differences. Results: The mean BMI was significantly higher among diabetic subjects compared to CAD patients with diabetes (p=0.001). HbA1c levels were also significantly elevated in diabetic patients (p=0.001). Adiponectin showed a negative correlation with BMI (r=-0.14) and a positive correlation with HbA1c (r=0.56) among CAD patients with diabetes mellitus. Conclusion: Altered adiponectin levels are significantly associated with obesity and glycemic status in CAD patients with type II diabetes mellitus. Adiponectin may serve as a potential biomarker for metabolic and cardiovascular risk assessment.